The science of memory, lies, and fiction how stories shape humanity's past, present, and future - Eusebio, Jerard Ancel D. (UP Los Baños Journal, 2020)
Why are humans—for all our evolutionary success—so invested in stories? From ancient tales to the latest tabloid fodder, from private diaries to Facebook Stories, we are steeped in stories. I make the case for how everything is stories, and for how stories are everything—from religion to philosophy to science. Using a transdisciplinary, biocultural approach that accounts for evolutionary literary criticism, philosophy, and the sciences—psychology, sociology, anthropology, neuroscience—I outline your engagement with stories and its impact on our identities, behaviours, decisions, social norms and structures, and, ultimately, our very survival and flourishing. Beginning with the human capacity for memory and prospection, I show how these—coupled with tendencies and incentives for lying—are fertile grounds for imagining and consuming alternate realities, as fiction. Finally, the single most important evolutionary purpose of stories, it appears, is in their capacity to facilitate massive human cooperation, by virtue of co-created realities such as nations, money, and religion. These structures, in turn, determine the lives we are able to build and the futures we are able to imagine. I draw upon the legislative journey of the divorce and the SOGIE equality bills in predominantly Catholic Philippines to illustrate that, while dominant narratives re able to prevail as they do, effective counter-narratives retain their potential to change society. Indeed, stories—in fiction in particular—are integral to our future, as individuals, as communities, as nations, and as a species: When we get our story right, we get our future right.